What hair it that”? an anthropological narrative about afro hair technologies in the diaspora - Santos, Luane Bento dos (Cadernos de Campo (São Paulo, 1991), 2023)
The aim of this article is to discuss the researcher's career in the field of Social Anthropology and Ethnic-Racial Relations. To this end, the article describes the processes of intellectual elaboration and ethnographic investigations that the researcher undertook during her research. The paper presents the main concerns and questions that arose during the research. The themes addressed in the text are the processes of constructing black identity based on the body and hair and the claims of the workers known as braiders and afro braiders, as an occupational category distinct from hairdressers. The research methods and techniques used were: ethnography, participant observation, semi-structured interviews, literature review and bibliographic survey